Introduction to research in education - Ary, Donald; Jacobs, Lucy Cheser; Sorensen, Christine Knupp; Walker, David A. (Cengage, 2019)
Helps students master the basic competencies necessary to understand and evaluate the research of others, and shows them how to plan and conduct original research. This book builds on the text's strengths of teaching students to become more competent consumers and producers of research